Building a research partnership between computer scientists and health service researchers for access and analysis of population-level health datasets: what are we learning?. (8th November 2019) - Schull, Michael; Brudno, Michael; Ghassemi, Marzyeh; Gibson, Garth; Goldenbrg, Anna; Paprica, Alison; Rosella, Laura; Stukel, Therese; Victor, Charles; Virtanen, Carl
No abstract available